Learning To Bonitize Breeding Camels (Eurasian Research Bulletin, 2024)
This article provides information on the bonitization of breeding animals, specifically camels, including only purebred camels and their hybrids. It discusses methods for assessing their breeding qualities and determining which class they belong to